Liver Metastases From Renal Oncocytoma With Vascular Extension. Issue 5 (May 2019) - Cacciamani, Giovanni; Cima, Luca; Ficial, Miriam; Novella, Giovanni; Siracusano, Salvatore; Tedeschi, Umberto; Balzarro, Matteo; Montin, Umberto; Cerruto, Maria A.; De Marco, Vincenzo; Porcaro, Antonio B.; Hes, Ondrej; et al.
Abstract : The 2016 World Health Organization Renal Tumor Classification defines renal oncocytoma (RO) as a benign epithelial tumor; however, malignant histopathologic features have been documented. Rare cases with metastases have been reported. We describe the case of a 62-year-old woman who was referred to the Urology Clinic for a routine work-up. Magnetic resonance imaging and computerized tomography showed a 7-cm mass in the middle and lower portions of the left kidney and 2 suspected liver metastases. The patient underwent surgery. Microscopically both renal and liver lesions presented solid, solid-nested, and microcystic architecture, composed predominantly of large eosinophilic cells without any worrisome pattern except the vascular extension. The cells were positive for S100A1, CD117, and PAX-8 and negative for CAIX, CK7, and AMACR. Fluorescence in situ hybridization showed a disomic profile for the chromosomes 1, 2, 6, 7, 10, 17. No mutation of coding sequence of the SDHB, SDHC, SDHD, VHL, and BHD genes and no loss of heterozygosity at 3p were found. The final diagnosis was "RO" according to the 2016 World Health Organization Renal Tumor Classification with "liver metastases." This report provides a wide clinical-pathologic, immunophenotypical and molecular documentation of a RO with liver metastases.